2010
DOI: 10.1021/ma101945f
|View full text |Cite
|
Sign up to set email alerts
|

Double Reaction-induced Microphase Separation in Epoxy Resin Containing Polystyrene-block-poly(ε-caprolactone)-block-poly(n-butyl acrylate) ABC Triblock Copolymer

Abstract: Polystyrene-block-poly(ε-caprolactone)-block-poly(n-butyl acrylate) (PS-b-PCL-b-PBA) triblock copolymer was synthesized through the combination of atom transfer radical polymerization, copper-catalyzed Huisgen 1,3-dipolar cycloaddition and ring-opening polymerization. The PS-b-PCL-b-PBA ABC triblock copolymer was incorporated into epoxy to access the nanostructures in the thermoset. The microphase-separated morphology was investigated by means of atomic force microscopy (AFM), small-angle X-ray scattering (SAX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…The nanophases are not formed until the curing reaction occurs with the sufficiently high conversion of the precursors. In the past decade, there have been a great number of reports on the preparation of the nanostructured thermosets by using a variety of block copolymers via self-assembly or RIMPS approach [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It is realized that thermosets can be significantly toughened via the formation of the nanostructures; the mechanisms of toughness improvement are attributable to the debonding of micelles (or vesicles) from thermosetting matrix, crack deflection or frictional interlocking in the thermosets displaying the terraced morphology [22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The nanophases are not formed until the curing reaction occurs with the sufficiently high conversion of the precursors. In the past decade, there have been a great number of reports on the preparation of the nanostructured thermosets by using a variety of block copolymers via self-assembly or RIMPS approach [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It is realized that thermosets can be significantly toughened via the formation of the nanostructures; the mechanisms of toughness improvement are attributable to the debonding of micelles (or vesicles) from thermosetting matrix, crack deflection or frictional interlocking in the thermosets displaying the terraced morphology [22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As a result, a higher cross-link density of the thermoset usually promises a higher T g when a hardener is fixed [31]. Meanwhile, different research groups [31,41,53,103] have reported an increased T g of their system with the introduction of different specific block copolymers, which is unexpected and not fully understood. This is attributed to the plasticization effect of miscible subchains in the copolymer that stretch out freely in the cured network [27,29,109].…”
Section: Glass Transition Temperaturementioning
confidence: 99%
“…Fan et al 58 synthesized a PS-block-PCL-block-poly(n-butyl acrylate) (PBA) triblock copolymer to access nanostructures in ER. It was found that depending on the concentration of the triblock copolymer, several types of nanophases were formed in the thermosets.…”
Section: Content Of the Reactive Polymermentioning
confidence: 99%